The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1088/2051-672x/ab8ffb
|View full text |Cite
|
Sign up to set email alerts
|

Computational evaluation of dynamic coefficients of thrust bearings; effect of artificial texturing on thermohydrodynamic performance

Abstract: Fluid film thrust bearings are commonly used in industry, providing durable and reliable operation at high values of load carrying capacity, accompanied by low friction losses. A major advantage of hydrodynamic fluid film bearings, over other types of bearings, is their enhanced dynamic behaviour, especially under transient or impact loads. Currently, a systematic approach to identify the dynamic coefficients of thrust bearing geometrical configurations utilising high complexity CFD simulation data has not yet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…In this technique, the journal center is perturbed from its equilibrium position, as demonstrated in figure 2. Thereafter, the changes in air film forces are computed for finding the dynamic performance parameters [58].…”
Section: Governing Equations For Dynamic Performancesmentioning
confidence: 99%
“…In this technique, the journal center is perturbed from its equilibrium position, as demonstrated in figure 2. Thereafter, the changes in air film forces are computed for finding the dynamic performance parameters [58].…”
Section: Governing Equations For Dynamic Performancesmentioning
confidence: 99%
“…Therefore, the improvement of lubrication performance and the reduction of wear are the key problem required to be solved urgently for water lubricated bearings. Surface texturing is an effective method to improve tribological performances of contacting surface, which has been widely used in many mechanical components [3][4][5][6][7]. Experimental studies reveal that the reasonable distribution and geometric parameters of texture are capable for enhancing the load capacity, yielding larger hydrodynamic pressure, reducing coefficient of friction(COF) and wear rate [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, numerous studies have shown that non-smooth surfaces have great potential in improving the lubrication and wear resistance of friction pairs [18][19][20]. Specifically, the main functions of surface textures/topographies can be classified into several types according to different lubrication states: (1) under mixed to dry friction, acting as traps to capture wear debris and reducing resistance and adhesion [21]; (2) under mixed to boundary lubrication, providing micro-reservoirs and resulting in numerous micro-fluid film bearings to enhance lubrication of friction pairs [22]; (3) under hydrodynamic lubrication, generating hydrodynamic pressure to increase the load-carrying capacity [23,24]. Among them, the main function mechanism of surface texture/topography under hydrodynamic lubrication can be explained as follows: In hydrodynamic lubrication, positive pressure will be generated when fluid flows along a convergent gap, but not along a divergent gap.…”
Section: Introductionmentioning
confidence: 99%
“…(2) under mixed to boundary lubrication, providing micro-reservoirs and resulting in numerous microfluid film bearings to enhance lubrication of friction pairs [22]; (3) under hydrodynamic lubrication, generating hydrodynamic pressure to increase the loadcarrying capacity [23,24]. Among them, the main function mechanism of surface texture/topography under hydrodynamic lubrication can be explained as follows: In hydrodynamic lubrication, positive pressure will be generated when fluid flows along a convergent gap, but not along a divergent gap.…”
Section: Introductionmentioning
confidence: 99%